Evaluation and Improvement of Nuclear Security Measures at a Radiological Facility in Morocco - Halima Jemmal; Abdelmajid Choukri; Mohammed Mouhib (International Journal of Nuclear Security, 2021)
Nuclear security combines both concepts of physical security and security culture within a nuclear facility to protect people, property, society and the environment from harmful effects of ionization radiation. Physical security means prevention, detection, and response to unauthorized removal, sabotage, and/or illegal transfer involving radioactive sources and nuclear material. Nuclear security culture is the human factor within the nuclear field which is considered a principal means to support and enhance nuclear security system. This paper presents a study of nuclear security system already established within a radiological facility considering concepts such as: deter, detect, delay, and response layers. This study focuses on nuclear security culture in order to assess, improve, and complement existing nuclear security practices.
Keywords: nuclear security; irradiation; ionization; security system; radiological; security culture; Cobalt-60